PENGARUH INVESTASI, TENAGA KERJA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROPINSI JAWA TIMUR - Sayekti Suindyah D (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
Investment, labor and government expenditure are important component for sustainable economic development process. This research aims is to analyze the effect of investment, labor, and government expenditure on Economic Growth in East Java Province. The hypotheses in this research is the investment, labor and government expenditure have influenced positive and significantly to the economic growth. Base on the data analysis, hypotheses is really accepted. This research shows that variable investment, labor and government expenditure have influence positive and significantly on economic growth. This indicates that three variables (investment, labor and government expenditure) have give contribution on economic growth is positively. This means if investment, labor and government expenditure are increasing because of grow up in economic growth in East Java Province. It is recommended that to increase economic growth of East Java Province, a police is needed to motivate all parties to make investment to this province. The effort to increase investment should be focused on activities that involve many workers. Therefore, it is recommended that to increase economic growth of East Java Province use to a police for motivate all parties to make investment, increase to labor quality and be careful to use a government expenditure.